PENGARUH ASIMETRIS INFORMASI, KESESUAIAN KOMPENSASI, KOMPETENSI DAN PERILAKU TIDAK ETIS TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Pada OPD Provinsi Riau) - Gita, Yolanda; Rasuli, M; Edfan, Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to look at the effect of asymmetry of information, compensation conformity, competency and unethical behavior on accounting fraud trends. This research was conducted at the OPD in Riau Province. The sampling technique used was purposive sampling. This research is included in quantitative research. In this research, there are five variables consisting of four independent variables, namely asymmetry of information, compensation conformity, competency and unethical behaviour and one dependent variable, namely accounting fraud trends. The source of data in this study is primary data. Data was collected using a questionnaire and distributed to 105 respondents but only 96 questionnaires could be processed. Data analysis method using Regression with the help of SPSS version 25. The results of this research showed that asymmetry of information, competency and unethical behavior have a affect on accounting fraud trends. While the compensation conformity have no affect to accounting fraud trends.Keywords: Asymmetry Of Information, Compensation Conformity, Competency, Unethical Behaviour, Accounting Frauds Trends